2012
DOI: 10.1074/jbc.m111.302588
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterial Transcriptional Regulator whiB7 Gene Links Redox Homeostasis and Intrinsic Antibiotic Resistance

Abstract: Background:The whiB7 gene is a multidrug resistance determinant in mycobacteria. Results: WhiB7 autoregulates its own promoter in response to both antibiotics (in a structure-and target-independent manner) and to redox changes. Conclusion: WhiB7 links cell metabolism, redox homeostasis, and antibiotic resistance. Significance: Understanding antibiotic-induced metabolic stress responses in mycobacteria may lead to therapies for mycobacterial diseases, including tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(194 citation statements)
references
References 44 publications
5
185
2
2
Order By: Relevance
“…Finally, for 1 of the 38 resistant clones without a mutation in atpE and atpB, selected on 0.5 mg/liter of TMC207, the sequences of the genes encoding the complete ATP synthase operon (F O and F 1 domains) were all found to be wild type compared to the reference sequence from H37Rv, highlighting that mechanisms not related to mutations in the ATP synthase operon can also contribute to resistance to TMC207 in M. tuberculosis and M. abscessus. Alternative hypotheses can be formulated to explain the resistance observed in the nonmutated clones, which include inactivation of the drug (a mechanism that cannot be excluded) or, alternatively, a change in pleiotropic transcriptional regulators affecting the intrinsic resistance of mycobacteria, such as WhiB7, affecting cellular metabolism (6). Further investigations about the possible other mechanisms of resistance to TMC207 are under way to elucidate this point.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for 1 of the 38 resistant clones without a mutation in atpE and atpB, selected on 0.5 mg/liter of TMC207, the sequences of the genes encoding the complete ATP synthase operon (F O and F 1 domains) were all found to be wild type compared to the reference sequence from H37Rv, highlighting that mechanisms not related to mutations in the ATP synthase operon can also contribute to resistance to TMC207 in M. tuberculosis and M. abscessus. Alternative hypotheses can be formulated to explain the resistance observed in the nonmutated clones, which include inactivation of the drug (a mechanism that cannot be excluded) or, alternatively, a change in pleiotropic transcriptional regulators affecting the intrinsic resistance of mycobacteria, such as WhiB7, affecting cellular metabolism (6). Further investigations about the possible other mechanisms of resistance to TMC207 are under way to elucidate this point.…”
Section: Discussionmentioning
confidence: 99%
“…Although this seems a reasonable assumption, it has not been confirmed experimentally. Thus, it remains possible that a transcription factor other than SigA is involved in promoting transcription from this Beijing-specific promoter region, or if SigA is involved, it may be doing so in the presence of an additional transcriptional activator (56).…”
Section: Fig 6 the Dost Defect In Beijing Isolates Has No Impact On Tmentioning
confidence: 99%
“…This is also interesting in light of the precedent in the literature that implicates the WhiB3 and WhiB7 transcription factors in modifying M. tuberculosis drug susceptibility. Like DosR, both of these transcription factors are known to regulate the cellular response to redox stress (56,68).…”
Section: Fig 6 the Dost Defect In Beijing Isolates Has No Impact On Tmentioning
confidence: 99%
“…While the regulatory mechanisms governing these gene expression changes have not been completely described, there is some evidence for transcriptional regulation of EPs. In this regard, it has been shown that WhiB7, a redox-sensitive transcriptional activator, plays an important role in mediating intrinsic drug resistance in mycobacteria, in some cases through direct regulation of EPs (147)(148)(149). Similarly, resistance to INH has been associated with the IniBIniA-IniC efflux system (Table 1), which is regulated by the MtrAB two-component system (150), and the mmr-encoded EP is regulated by a TetR-type repressor (151).…”
Section: Energy Metabolism and Drug Effluxmentioning
confidence: 99%